ACTIVE LEARNING VS. DRAMA IN ELEMENTARY SCIENCE - Nesil TIMBIL (Fırat University, 2019)
The present study aimed at examining the effects of active learning and drama on science achievement. In order to do that the subject of “Matter and Energy for Living Things” was chosen. An achievement test on the subject was applied as pre-test to the 8th grade students in a public school in a small town. After getting information from the teachers and administrator and also based on the test scores, two classes (high achievers, low achievers) were selected as a sample. Each class was